Woodcraft markets in Zimbabwe - Braedt, O.; Standa-Gunda, W. (2000)
To understand the potential role of forest products in household livelihoods, a study of the woodcraft industry in Zimbabwe was initiated. The woodcraft industry has increased steadily since the late 1980s. The factors driving the upsurge in the woodcraft industry are: (1) the increased demand by tourists; and (2) the need by rural households to find cash income sources. The structural adjustment programme, with one of its emphases being the decontrol of the currency, has probably played a key role in driving the rise in woodcraft production. Although all markets have a committee and all have some basic rules governing their operations, few rules are strictly enforced. There is also a lack of enforcement of the national legislation that governs the use of the tree resources. The local traditional rules governing resource use from the commons are also not strong. Given the problems in the national legislation and in the local rules, it is difficult to see how the resource can be managed on a sustainable basis. It appears that the benefits from the industry may not be substantial given the lack of interest in the market from outsiders, and the various elites who could monopolise the trade due to the lack of enforcement structures in place. In communal areas, where deforestation is advanced, the selective use of certain species for carving is likely to drive the species to local extinction. The carvers are likely to switch to different tree species to maintain their production levels.